2019
DOI: 10.1371/journal.pone.0225912
|View full text |Cite
|
Sign up to set email alerts
|

L-lysine protects C2C12 myotubes and 3T3-L1 adipocytes against high glucose damages and stresses

Abstract: Hyperglycemia is a hallmark of diabetes, which is associated with protein glycation and misfolding, impaired cell metabolism and altered signaling pathways result in endoplasmic reticulum stress (ERS). We previously showed that L-lysine (Lys) inhibits the nonenzymatic glycation of proteins, and protects diabetic rats and type 2 diabetic patients against diabetic complications. Here, we studied some molecular aspects of the Lys protective role in high glucose (HG)-induced toxicity in C2C12 myotubes and 3T3-L1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Roles of autophagy in NAFLD remain controversial. Drugs against NAFLD by either increasing autophagy or inhibiting autophagy were reported ( Chu et al, 2019 ; Ebrahimi et al, 2019 ; Ren et al, 2019 ). We observed that NAR induced autophagy and promoted the initiation of autophagy in autophagic flux in 3T3-L1 preadipocytes and C2C12 myoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Roles of autophagy in NAFLD remain controversial. Drugs against NAFLD by either increasing autophagy or inhibiting autophagy were reported ( Chu et al, 2019 ; Ebrahimi et al, 2019 ; Ren et al, 2019 ). We observed that NAR induced autophagy and promoted the initiation of autophagy in autophagic flux in 3T3-L1 preadipocytes and C2C12 myoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…[ 32 ] Depending on this mechanism, L‐lysine has been an effective medicine against high‐glucose damages and stresses. [ 33 ] As displayed in Figure 6h , compared to ARC, the intensity of proly‐Lysine ( m / z 266.21, [M + Na] + ) is significantly down‐regulated in CHM, which is possibly related to the high concentration of glucose. Meanwhile, the approximate down‐regulation of proly‐Lysine in CDM is also observed, indirectly echoing with the consistency of change trend of glucose concentration in CDM and CHM (Figure 6d ) and manifesting the menace of diabetes toward cataracts again.…”
Section: Resultsmentioning
confidence: 99%
“…Lysine is an essential amino acid critical for normal growth in animals ( 51 ). The addition of lysine can significantly reduce the level of ROS induced by high glucose in C2C12 myotubes and 3T3-L1 adipocytes and can regulate the unfolded protein response and autophagy ( 52 ). Previous studies have shown that d -pipecolic acid in plasma originates from the catabolism of dietary lysine in the intestine.…”
Section: Discussionmentioning
confidence: 99%